2017
DOI: 10.12965/jer.1734978.489
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of cancer center programs in Korea

Abstract: This study was conducted to investigate cancer centers established for the purpose of satisfying various needs about cancer, improving the cancer treatment environment, and subdividing services ranging from diagnosis, treatment, and rehabilitation to palliative care. To this end, the authors have surveyed programs in 17 cancer centers representing Korea, including 12 national cancer centers and five major hospitals. As a result, it was found that the most common type of lecture program was disease management, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Negative exercise recognition affects the obstructions owing to the less-than-expected exercise programs for cancers. In this regard, previous works [ 24 , 25 ] have reported that patients were reluctant to take part in an exercise program if the program was contrary to their expectations. Generally, patients with cancers or other serious diseases have high expectations of diverse interventional treatments, including exercise, nutrition, and supplements, due to their strong desire to extend and recover life.…”
Section: Discussionmentioning
confidence: 97%
“…Negative exercise recognition affects the obstructions owing to the less-than-expected exercise programs for cancers. In this regard, previous works [ 24 , 25 ] have reported that patients were reluctant to take part in an exercise program if the program was contrary to their expectations. Generally, patients with cancers or other serious diseases have high expectations of diverse interventional treatments, including exercise, nutrition, and supplements, due to their strong desire to extend and recover life.…”
Section: Discussionmentioning
confidence: 97%
“…These results imply that the patients with positive exercise experience tend to rationalize the exercise program provided by the hospital even though it is insufficient, whereas negative exercise recognition adversely affects the exercise program for cancer patients if it does not meet the expectation of the patients. In this regard, Schwartz (1999) and Kim and Yi (2017) reported that the patients were reluctant to participate in the program if their exercise program did not meet the expectations of the patients. Because the patients with serious disease such as cancer have stronger will to extend life expectancy and to recover than patients with general diseases, they tend to have greater expectations on various interventions such as nutrition and supplements including exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Factors prohibiting rehabilitation treatment despite its demand include not only the absence of the appropriate referring system, but also the fact that clinicians do not recognize the need for rehabilitation and do not adequately prescribe or connect it [ 5 ]. According to a nationwide survey of cancer center programs in Korea, the types and methods of rehabilitation provided by cancer centers significantly differed based on regions and cancer type [ 9 , 10 ]. For example, more than 60% of patients with breast cancer, brain tumors, and spinal tumors receive rehabilitation services.…”
Section: Introductionmentioning
confidence: 99%